Training and Assistance of Village-Owned Enterprises (BUMDES) Financial Reporting in Kekeri Village, West Lombok - Priyambodo, Victoria K.; Jumaidi, L. Takdir; Sukma, Paradisa (Talenta Publisher, 2023)
Village-Owned Enterprises (BUMDES) Inti Sejahtera is located in Kekeri Village, Gunungsari, West Lombok, West Nusa Tenggara. It has three activity units, including a waste management unit, a development unit, and a trade unit. Of the three existing units, only the waste management unit operates adequately and generates regular income for BUMDes. BUMDes encounters issues in terms of financial management and preparing financial reports that are transparent and adhere to accounting principles. Transaction recording is still conducted manually, hence posing challenges in preparing the necessary financial reports. On the other hand, BUMDes funding comes from PADes, so BUMDes must provide financial reports to the village government as a form of accountability. This community service aims to resolve financial management limitations at BUMDes Inti Sejahtera by providing training and assistance to managers regarding the preparation of BUMDes financial reports. The method carried out is identifying problems in BUMDes (pre-training stage), then providing practical training and assistance in preparing financial reports according to accounting principles using the Microsoft Excel Macro application, which is adapted to BUMDES transaction accounts, as well as conducting evaluation reviews and monitoring of reports prepared by the manager. The outcome of this activity is that BUMDes managers acquire the capability to independently enter transactions and make account adjustments. Furthermore, the results suggest that BUMDes managers possess the necessary knowledge and skills to prepare financial reports in accordance with accounting principles by utilizing the Microsoft Excel macro-application. It can be concluded that BUMDes Inti Sejahtera managers can improve their accounting skills and use technological information to prepare and present BUMDes financial reports.